The role of histone arginine methylation in cytokine/chemokine gene expression in airway smooth muscle cells in asthma - Kaczmarek, Klaudia (2019)
Background: Asthma is a common chronic condition, which has a negative impact on life quality of those suffering and is also a burden to the national healthcare. Airway smooth muscle (ASM) cells have a crucial role in asthma, contributing to airway remodelling, airflow obstruction, and inflammation of the airways. Epigenetic changes, particularly histone lysine acetylation/methylation, have been shown to alter ASM functions. Histone arginine modifications have been less well studied.